THE IMPORTANCE OF SALT EXPLOITATION IN ROMAN DACIA. THE CASE OF OCNA MUREȘ (SALINAE) - Lucrețiu Mihailesu-Bîrliba (Journal of Ancient History and Archaeology)
The current paper presents a part of the epigraphic file of Ocna Mureș (the ancient Salinae), taking into account the brick stamps containing the name of the legio XIII Gemina and the names of magistri figlinae. Putting together the epigraphic evidences, the author shows the importance of the salt exploitation at Ocna Mureș for the Roman army.